2021
DOI: 10.1016/j.cjco.2020.09.016
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Right Ventricular Dysfunction on Mortality in Patients Hospitalized With COVID-19, According to Race

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 29 publications
5
70
0
6
Order By: Relevance
“…As a result, RVD is associated with worse outcomes in the context of COVID-19 disease. 35 , 56 This remains very difficult to manage and future research should be directed at ways of protecting the RV before dysfunction develops, monitoring of RVD and response to treatment, echocardiographic and hemodynamic RVD phenotyping and effective management of established RV failure in patients with severe COVID-19 disease.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, RVD is associated with worse outcomes in the context of COVID-19 disease. 35 , 56 This remains very difficult to manage and future research should be directed at ways of protecting the RV before dysfunction develops, monitoring of RVD and response to treatment, echocardiographic and hemodynamic RVD phenotyping and effective management of established RV failure in patients with severe COVID-19 disease.…”
Section: Resultsmentioning
confidence: 99%
“…Widespread small pulmonary arteriolar fibrin thrombi and widespread alveolar capillary thrombi specific to COVID-19, compared with influenza cases, support the concept that RV dilatation is partly due to pressure overload. (Huang et al, 2020b;Moody et al, 2020;Stockenhuber et al, 2020) TAPSE was shown to be associated with the pulmonary embolism occurence in patients with COVID-19. (Scudiero et al, 2021) Myocardial injury and hyperinflammation in COVID-19-induced cytokine storm could be an additional cause of ARDS-related acute RHF.…”
Section: Discussionmentioning
confidence: 99%
“…HScTn is a powerful prognostic marker in COVID-19, with multiple potential causes, including myocarditis, coronary microvascular ischemia, stress cardiomyopathy, and tachycardiomyopathy. (Moody et al, 2020) Patients with proven myocardial damage are advised to undergo echocardiography as initial cardiac imaging, which appears to substantially alter clinical management in one-third of patients. (Stockenhuber et al, 2020) Likely echocardiography findings are: (1) swollen heart mostly due to pericardial effusion, characterized by excessive cardiac weight, thickened biventricular walls, and subsequent increase in biventricular mass; (2) hemodynamic disorder, reflected as reduced cardiac output and increased LV filling pressure; and (3) functional impairment, most commonly seen as RV systolic dysfunction rather than LV, with pulmonary hypertension and RV enlargement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their echocardiographic study, Moody et al have found an independent association between reduced RV systolic dysfunction and all-cause mortality in severe COVID-19 patients with elevated TnT. Besides the effects of thromboembolic disease, authors hypothesized a possible primary RV involvement as a concurrent factor to RV injury [ 35 ]. In this clinical setting, a significant contribution could be provided by CMR, which has shown to be the gold standard for the evaluation of RV function together with tissue characterization [ 36 ].…”
Section: Myocarditismentioning
confidence: 99%